Colónias Agrícolas Portuguesas construídas pela Junta de Colonização Interna entre 1936 e 1960. A casa, o assentamento, o território - Filipa de Castro Guerreiro (2016)
The seven agricultural colonies built by the Internal Colonization Board (ICB) in continental Portugal between 1936 and 1960 are the subject of the research. Noting that there is, from a disciplinary architectural point of view, a widespread ignorance of the existence of ICB's agricultural colonies; that among the several colonies and even within each colony there is a diversity of models of territorial structuring, settlement framing and expressions of building architecture, which contradicts the artificially established vision on the work of the public organisms of the New State; and that, by visiting the seven colonies, one can sense the existence of principles and spatial devices which enable the recognition of an identity and a mutual territorial legibility; it is proposed: - the identification of the seven agricultural colonies, for which cartography, to territorial scale, thus far inexistent, was elaborated, identifying the extent of the agricultural land of each nucleus and the implementation of the settlement; the drawings of the settlements, referencing all the buildings (with date and authors indicated); and the survey of the buildings of agricultural couples; - the contextualization of the shaping and objectives of the ICB, enlisting its action in the debate on land reform, initiated in the mid-19th century. The analysis of ICB's activity, through their projects and achievements and its relationship with the legal framework in which they fell, as well as the social and political contexts on which the ICB exerted influence; - the interpretation of the diversity of conformations mentioned above from the fact that the constitution and configuration of the agricultural colonies do not correspond to a single, punctual and closed project, but instead a result of a long process which encompasses various visions and programs that emerged from the various stages of formation and maturation of the ICB itself. In this sense we circumscribe four key moments of the construction process of the agricultural colonies of ICB. For each moment, we place a hypothesis of reconstruction of the context and objectives of the order, and analyze, in each scale - territory, settlement and house -, premises, programs, dimensioning, principles of composition, references, influences and similarities of themes. This analysis allows us to, among other, understand the existence of different architectural order constraints, arising from changes in the economic and socio-political context; of variations in training of technical teams; and occasionally of space for an individual contribution on the part of technicians. It allows us also to affirm that for most of the construction of agricultural colonies of the ICB, their projects reflect the themes of the architectural debate of its period. Themes with which the architects of the ICB also struggled with, and in some ways, even if they have not had dimension, dissemination and visibility to be a model, example or reference, were precursors; - the measuring principles, strategies and constructed elements that introduce legibility in the colonies and that allow the recognition of a common identity. The questioning of the inscription of this set of interventions in the culture of Portuguese urban spaces and its possible contribution to the development of projects of agricultural colonization of Angola and Mozambique, undertaken between 1950 and 1960. Studying the agricultural colonies of ICB was for us, first of all, a project exercise in architecture, for which we use our usual tools, in particular the drawing as a means of interpretation and synthesis. The analogies that we found between the themes of design of the agricultural colonies of the ICB and the issues that characterize today the rural depopulated and extensively urbanized territory allow us to consider that learning from the experience of the ICB constitutes a rich and operative contribution for the project exercise in contemporary territory.